Abscisic acid‐controlled redox proteome of Arabidopsis and its regulation by heterotrimeric Gβ protein. Issue 2 (19th July 2022) - Smythers, Amanda L.; Bhatnagar, Nikita; Ha, Chien; Majumdar, Parinita; McConnell, Evan W.; Mohanasundaram, Boominathan; Hicks, Leslie M.; Pandey, Sona
Summary: The plant hormone abscisic acid (ABA) plays crucial roles in regulation of stress responses and growth modulation. Heterotrimeric G‐proteins are key mediators of ABA responses. Both ABA and G‐proteins have also been implicated in intracellular redox regulation; however, the extent to which reversible protein oxidation manipulates ABA and/or G‐protein signaling remains uncharacterized. To probe the role of reversible protein oxidation in plant stress response and its dependence on G‐proteins, we determined the ABA‐dependent reversible redoxome of wild‐type and Gβ‐protein null mutant agb1 of Arabidopsis. We quantified 6891 uniquely oxidized cysteine‐containing peptides, 923 of which show significant changes in oxidation following ABA treatment. The majority of these changes required the presence of G‐proteins. Divergent pathways including primary metabolism, reactive oxygen species response, translation and photosynthesis exhibited both ABA‐ and G‐protein‐dependent redox changes, many of which occurred on proteins not previously linked to them. We report the most comprehensive ABA‐dependent plant redoxome and uncover a complex network of reversible oxidations that allow ABA and G‐proteins to rapidly adjust cellular signaling to adapt to changing environments. Physiological validation of a subset of these observations suggests that functional G‐proteins are required to maintain intracellular redox homeostasis and fully execute plant stress responses.